Las alternativas disponibles en el manejo de poblaciones y familias segregantes (F2 y pruebas de descendencia hasta F6). Selecciones individuales vrs. masales, decisiones de manejo - Rodríguez, R. (Programa Cooperativo Regional de Frijol para Centroamérica, México y el Caribe (PROFRIJOL), 1989)
The genealogical or pedigree and the bulk cross methods, used to produce hybrid bean materials, are described. The characteristics and advantages of screening methods used to select individuals with desirable characteristics are indicated. Methods include individual or pure line selection and mass selection or mixture of pure lines. Aspects are considered regarding population size to perform genotype segregation; yield components should be measured in order to compare the progress of selected populations over their parents. (CIAT)